High-resolution Ceres Low Altitude Mapping Orbit Atlas derived from Dawn Framing Camera images. (June 2017) - Roatsch, Th.; Kersten, E.; Matz, K.-D.; Preusker, F.; Scholten, F.; Jaumann, R.; Raymond, C.A.; Russell, C.T.
Abstract: The Dawn spacecraft Framing Camera (FC) acquired over 31, 300 clear filter images of Ceres with a resolution of about 35 m/pxl during the eleven cycles in the Low Altitude Mapping Orbit (LAMO) phase between December 16 2015 and August 8 2016. We ortho-rectified the images from the first four cycles and produced a global, high-resolution, uncontrolled photomosaic of Ceres. This global mosaic is the basis for a high-resolution Ceres atlas that consists of 62 tiles mapped at a scale of 1:250, 000. The nomenclature used in this atlas was proposed by the Dawn team and was approved by the International Astronomical Union (IAU). The full atlas is available to the public through the Dawn Geographical Information System (GIS) web page [http://dawngis.dlr.de/atlas ] and will become available through the NASA Planetary Data System (PDS) (http://pdssbn.astro.umd.edu/ ). Highlights: The mosaic of Ceres was created using camera data from LAMO orbit phase. An atlas of Ceres consisting of 62 tiles was created. The nomenclature for surface features was approved by the IAU and applied to the atlas.